Factors Associated with Retention of HIV Patients on Antiretroviral Therapy in Care: Evidence from Outpatient Clinics in Two Provinces of the Democratic Republic of the Congo (DRC) - Gulzar H. Shah; Gina D. Etheredge; Lievain Maluentesa Nkuta; Kristie C. Waterfield; Osaremhen Ikhile; John Ditekemena; Bossiky Ngoy Belly Bernard (Tropical Medicine and Infectious Disease, 2022)
Interruptions in the continuum of care for HIV can inadvertently increase a patient’s risk of poor health outcomes such as uncontrolled viral load and a greater likelihood of developing drug resistance. Retention of people living with HIV (PLHIV) in care and determinants of attrition, such as adherence to treatment, are among the most critical links strengthening the continuum of care, reducing the risk of treatment failure, and assuring viral load suppression. Objective: To analyze the variation in, and factors associated with, retention of patients enrolled in HIV services at outpatient clinics in the provinces of Kinshasa and Haut-Katanga, Democratic Republic of the Congo (DRC). Methods: Data for the last visit of 51,286 patients enrolled in Centers for Disease Control (CDC)-supported outpatient HIV clinics in 18 health zones in Haut-Katanga and Kinshasa, DRC were extracted in June 2020. Chi-square tests and multivariable logistic regressions were performed. Results: The results showed a retention rate of 78.2%. Most patients were classified to be at WHO clinical stage 1 (42.1%), the asymptomatic stage, and only 3.2% were at stage 4, the severest stage of AIDS. Odds of retention were significantly higher for patients at WHO clinical stage 1 compared to stage 4 (adjusted odds ratio (AOR), 1.325; confidence interval (CI), 1.13–1.55), women as opposed to men (AOR, 2.00; CI, 1.63–2.44), and women who were not pregnant (vs. pregnant women) at the start of antiretroviral therapy (ART) (AOR, 2.80; CI, 2.04–3.85). Odds of retention were significantly lower for patients who received a one-month supply rather than multiple months (AOR, 0.22; CI, 0.20–0.23), and for patients in urban health zones (AOR, 0.75; CI, 0.59–0.94) rather than rural. Compared to patients 55 years of age or older, the odds of retention were significantly lower for patients younger than 15 (AOR, 0.35; CI, 0.30–0.42), and those aged 15 and <55 (AOR, 0.75; CI, 0.68–0.82). Conclusions: Significant variations exist in the retention of patients in HIV care by patient characteristics. There is evidence of strong associations of many patient characteristics with retention in care, including clinical, demographic, and other contextual variables that may be beneficial for improvements in HIV services in DRC.